Spiritual Intervention to Improve Psychological Wellbeing on Cancer Patient: A Scoping Review - Iyus Yosep; Rohman Hikmat; Linlin Lindayani; Ai Mardhiyah (Journal of Nursing Care, 2022)
Cancer occurs due to the addition of mass in body cells that can spread and cause death. The problems arising from cancer are physical, psychological, and spiritual problems. Spiritual intervention is essential and valuable as one of the treatment efforts in dealing with issues caused by cancer. However, there are obstacles where nurses still need to be exposed to much information about spiritual intervention. The purpose of this study was to obtain an overview of spiritual intervention in cancer patients. This study uses the Scoping Review method. Literature review through Ebsco, Pubmed, Science Direct, and Sage Journals databases. The keywords used in English are Cancer, Spiritual intervention,” AND “Spiritual needs OR spiritual experience OR spirituality”. The criteria for articles in this study are full text, free access, randomized control trial or quasi-experiment research design, English language, population and samples of cancer patients, and the publication period of the last ten years (2013-2022). Found ten articles with different spiritual interventions on cancer patients. Two papers with mindfulness intervention, an article with a spiritual counselling intervention, 3 with spiritual intervention, 2 with spiritual therapy intervention, and 2 with spiritual care intervention. Five spiritual interventions for cancer patients can overcome problems caused by cancer, namely mindfulness, spiritual counselling, spiritual intervention, spiritual therapy, and spiritual care. Spiritual counselling is a very effective intervention because it is carried out intensively and comprehensively to maximize the psychological well-being of cancer patients.